2015
DOI: 10.18632/genesandcancer.84
|View full text |Cite
|
Sign up to set email alerts
|

A novel MeCP2 acetylation site regulates interaction with ATRX and HDAC1

Abstract: Methyl-CpG-binding protein-2 (MeCP2) regulates gene expression by recruiting SWI/SNF DNA helicase/ATPase (ATRX) and Histone Deacetylase-1 (HDAC1) to methylated gene regions and modulates heterochromatin association by interacting with Heterochromatin protein-1. As MeCP2 contributes to tumor suppressor gene silencing and its mutation causes Rett Syndrome, we investigated how novel post-translational-modification contributes to its function. Herein we report that upon pharmacological inhibition of SIRT1 in RKO c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…K171 has been recently proved to be acetylated 17 , whereas the ID has been demonstrated as a major site of poly(ADP-rybosyl)ation 18 . Both these PTMs highly impact on MeCP2 functions: K171 acetylation modulates the interaction of MeCP2 with ATRX and HDAC1, while (ADP-rybosyl)ation reduces the capability of MeCP2 to cluster heterochromatin 17 18 . By analyzing evolutional conservation, we noticed that S164 and S166 have been maintained from X. laevis to humans ( Fig.…”
mentioning
confidence: 99%
“…K171 has been recently proved to be acetylated 17 , whereas the ID has been demonstrated as a major site of poly(ADP-rybosyl)ation 18 . Both these PTMs highly impact on MeCP2 functions: K171 acetylation modulates the interaction of MeCP2 with ATRX and HDAC1, while (ADP-rybosyl)ation reduces the capability of MeCP2 to cluster heterochromatin 17 18 . By analyzing evolutional conservation, we noticed that S164 and S166 have been maintained from X. laevis to humans ( Fig.…”
mentioning
confidence: 99%
“…Histone deacetylases (HDACs) remove acetyl groups from histones, resulting in chromatin compaction and decreased accessibility to DNA for interacting molecules such as transcription factors, resulting in compaction of chromatin structure and transcriptional repression. HDACs operate by direct association with DNA-binding factors and by incorporation into large multifunctional repressor complexes such as Sin3, NuRD, and PRC2 [12]. In addition to functions in chromatin remodeling, HDACs deacetylate certain transcription factors, such as P53 [13], resulting in their decreased activity.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that MeCP2 undergoes acetylation on Lys-171 in both MCF7 and RKO cells. We further demonstrated that a K171 acetylation mimetic did not perturb binding to select gene targets, but it diminished interaction of MeCP2 with binding partners such as ATRX and HDAC1 in colorectal cancer cells (44). In vivo and in vitro studies have demonstrated the importance of MeCP2 post-translational regulation (45,(104)(105)(106)(107)), yet little has been done to comprehensively map novel MeCP2 PTMs.…”
Section: Endogenous Mecp2 Is Acetylated At Key Lysine Residues and Kdmentioning
confidence: 89%